Effect of Pinus elliottii plantations on seed removal along with fragments of Montana Mixed Ombrophilous Forest - Cury, Letícia Duron [UNESP]; Dos Santos Cury, Roberta Thays; Amorim, Felipe Wanderley [UNESP]; Campos, Sergio [UNESP]; de Barros, Ana Clara [UNESP]; da Silva, Leonardo França (My University, 2022)
The conversion of natural forests into homogeneous reforestation areas, when done with exotic species may influence ecological processes, such as the interaction between seeds and their natural predators and/or dispersers. Herein we evaluate whether the use of Pinus elliottii in homogeneous reforestation areas influences seed removal from the soil in the secondary vegetation of the adjacent Mixed Ombrophilous Montane Forest. Six areas of secondary vegetation from the Montana Forest, adjacent to P. elliottii crops, were selected and sampling points were distributed along transects 0, 10, 25, 50 and 100 meters from the forest edge. The removal rate was elevated for all species (100% for Syagrus romanzoffiana, 98% for Pinus elliottii and 49% for Araucaria angustifolia). Seeds of A. angustifolia presented increased removal rates towards the interior of native forest, with 33% of removal at 0 m and 70% at 100 m from the forest edge. The increase in seed removal indicates that fauna oftenly associated with the analyzed species may be related to both predation and secondary dispersion of seeds. We suggest that the reduced removal of A. angustifolia seeds, a key species for the Atlantic Forest, at the forest edge beside P. elliottii crops may indicate loss in movement from wild fauna associated with the homogeneous planting of trees. Also the removal of P. elliottii within the native forest, if predated, may indicate curbing of its invasive potential. However, if dispersed, it may indicate P. elliottii is, in fact, invading the Mixed Ombrophilous Montane Forest.
Efeito do plantio de Pinus elliottii na remoção de sementes ao longo de fragmentos de Floresta Ombrófila Mista Montana
Keywords: Atlantic Forest; Homogeneous reforestation; Secondary dispersion; Seed dispersion; Seed predation